High Gain Step Up DC-DC Converter at Lower Duty Cycle - C, NagaDevi; Janani J K, Sree Vidhya; A, Ishwarya T; S, Gurunandhini (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2021)
Micro-grid provides high efficiency, low cost and clean energy. Micro-grid comes on variety of design and sizes. Nowadays, DC micro-grid plays a vital role because of remarkable amplifying DC load. Photo voltaic source is the first source of energy. High voltage gain in Boost converter are limited by high duty cycle. This will leads to serious reverse recovery problem, high conduction loss etc. Isolated converter such as fly back, Bridge converter etc., since the above problem. But it uses transformer or coupled inductor which causes voltages spike at the main switch and power loss due to leakage inductance. The conventional Boost converter is compared with the high gain step-up DC-DC converter circuit. Thus results the, high gain with low duty cycle. The major important is we can supply power for two loads. Theoretical verification is done using MATLAB software. Where practical verification is done by Ardiuno connected with the isolated circuit and then connected with the main circuit.